Perancangan Manajemen Proyek Sistem Informasi Pengarsipan Surat Berbasis Website di Desa Katapang - Nugraha, Muhamad Fahmi; Hakim, Daffa Fauzul; Budiman, Tedi; Tryana, Anjas (Ma'soem University, 2024)
As the volume of data generated by various entities continues to grow, the challenges in managing and searching for data become increasingly complex, including in document and letter management within organizations. Desa Katapang, located in Katapang District, Bandung Regency, faces challenges in managing administrative letters and documents manually, which increases the risk of data loss and inaccuracies. To address this issue, a web-based letter archiving information system was developed to enhance efficiency, productivity, and document management security. This system enables digital storage, reducing the dependency on physical archives, and allows for fast and accurate document retrieval. In developing this system, the waterfall methodology was employed, covering stages such as needs analysis, system design, implementation, and testing. Additionally, project management was applied through the Work Breakdown Structure (WBS), Critical Path Method (CPM), and Program Evaluation and Review Technique (PERT) approaches to ensure the project is completed on time and within budget. The results of the study show that this project is feasible to implement, with an ROI (Return on Investment) of 1.4 and an IRR (Internal Rate of Return) of 41%. With this system, Desa Katapang can improve services to the community, optimize document management processes, and reduce the risks associated with manual archiving.